Crises within communism and temporary aid - Ernst Mohr (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
An explanation is given why communist economies usually react smoothly but sometimes very dramatically to seemingly minor changes in the political and economic environment. In this paper such dramatic reactions materialize in a sudden clamp-down on individual freedom and sudden economic prosperity or in quick political liberalization and a quick demise of economic success. Furthermore, the consequences of temporary economic aid in the face of these potential crises are analysed.
Keywords: 330; Kommunismus; Wirtschaftsreform; Internationale Wirtschaftshilfe; Theorie